NASOPHARYNGEAL CARCINOMA WITH INTRACRANIAL INVOLVED - Yamani Amouzegar, Ervin (TALENTA PUBLISHER, 2020)
Abstract Introduction: Nasopharyngeal carcinoma (NPC) is an aggressive carcinoma come from postnasal space. Histology type of nasopharyngeal cell carcinoma and the staging that affect with management therapy. Nasopharyngeal carcinoma can be controlled by implementing evidence-based strategies of cancer and management of patients. Case report: Reported a case in 47-year-old man, diagnosis squamous cell carcinoma of nasopharynx with intracranial involvement. Conclusion: Histology type of nasopharyngeal carcinoma and the staging determined the modality of therapy and nasopharyngeal carcinoma prognosis